Comparison of Neutralizing Antibody Responses Elicited from Highly Diverse Polyvalent Heterotrimeric HIV-1 gp140 Cocktail Immunogens versus a Monovalent Counterpart in Rhesus Macaques - Bowles, Emma J.; Schiffner, Torben; Rosario, Maximillian; Needham, Gemma A.; Ramaswamy, Meghna; McGouran, Joanna; Kessler, Benedikt; LaBranche, Celia; McMichael, Andrew J.; Montefiori, David; Sattentau, Quentin J.; Hanke, Tomáš; et al. (PLOS ONE, 2014)
Eliciting neutralizing antibodies capable of inactivating a broad spectrum of HIV-1 strains is a major goal of HIV-1 vaccine design. The challenge is that envelopes (Envs) of circulating viruses are almost certainly different from any Env used in a vaccine. A novel immunogen composed of a highly diverse set of gp140 Envs including subtypes A, B, C, D and F was developed to stimulate a more cross-neutralizing antibody response. Env heterotrimers composed of up to 54 different gp140s were produced with the aim of focusing the response to the conserved regions of Env while reducing the dominance of any individual hypervariable region. Heterotrimeric gp140 Envs of inter- and intra-subtype combinations were shown to bind CD4 and a panel of neutralizing monoclonal antibodies with similar affinity to monovalent UG37 gp140. Macaques immunized with six groups of heterotrimer mixtures showed slightly more potent neutralizing antibody responses in TZM-BL tier 1 and A3R5 tier 2 pseudovirus assays than macaques immunized with monovalent Env gp140, and exhibited a marginally greater focus on the CD4-binding site. Carbopol enhanced neutralization when used as an adjuvant instead of RIBI in combination with UG37 gp140. These data indicate that cross-subtype heterotrimeric gp140 Envs may elicit some improvement of the neutralizing antibody response in macaques compared to monovalent gp140 Env.